Extraction of curcumin from turmeric by ultrasonic-assisted extraction, identification, and evaluation of the biological activity - Wimonrut Insuan; Nanthiya Hansupalak; Thippayarat Chahomchuen (Shahrekord University of Medical Sciences, 2022)
Introduction: Dried rhizomes of turmeric have been traditionally used as a medicinal herb, dietary spice, food source, food preservative, and natural coloring agent in many Asian countries. This study aimed to develop the ultrasonic-assisted extraction (UAE) method for the extraction of curcumin from turmeric powder, evaluate the extraction efficiency, curcumin concentration, and biological activities.Methods: The UAE effects were examined based on several parameters of extraction efficiencies. The curcumin content was also determined using high-performance liquid chromatography (HPLC), and the total phenolic content (TPC) was estimated by Folin-Ciocalteu colorimetric method. The antibacterial activity of the extracted was evaluated against the test pathogenic bacteria by the disc diffusion method. The correlation between extraction yield and curcumin content was performed by principal components analysis (PCA).Results: The optimal UAE conditions were: ethanol, a solid-liquid ratio of 1:10 (w/v), an extraction time of 40 min, and only one extraction step. Under the optimal conditions, the yield of curcumin was 160.3 ± 1.17 (mg/g extract) and the TPC was 185.5 ± 3.07 (mg gallic acid equivalent /g extract). PCA presented the positive correlation between curcumin and the TPC of the studied extracts. Comparison of antibacterial activity between UAE and maceration method against the tested bacteria showed no significant difference at P > 0.05.Conclusion: UAE was a viable alternative as a rapid, efficient, and simple means of extraction of curcumin from turmeric. The extracts had great potential as a source of antioxidant agents with high amounts of curcuminoids, phenolic compounds and exhibited activity against pathogenic bacteria.